2014
DOI: 10.1007/s13277-014-2000-3
|View full text |Cite
|
Sign up to set email alerts
|

CKAP4 inhibited growth and metastasis of hepatocellular carcinoma through regulating EGFR signaling

Abstract: CKAP4, one kind of type II trans-membrane protein, plays an important role to maintain endoplasmic reticulum structure and inhibits the proliferation of bladder cancer cells by combining its ligand anti-proliferative factor (APF). However, the biological function of CKAP4 in the progression of liver cancer has not been clearly demonstrated. In the present study, we knocked down or overexpressed CKAP4 in hepatocellular carcinoma (HCC) cells and cell proliferation, invasion, and migration capacities were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…5E and F). Overexpression of CKAP4 increased E-cadherin expression, which is consistent with previous report [22]. MYCT1 overexpression abolished the CKAP4-mediated E-cadherin up-regulation ( Fig.…”
Section: Ckap4 Interacts With Myct1supporting
confidence: 93%
See 1 more Smart Citation
“…5E and F). Overexpression of CKAP4 increased E-cadherin expression, which is consistent with previous report [22]. MYCT1 overexpression abolished the CKAP4-mediated E-cadherin up-regulation ( Fig.…”
Section: Ckap4 Interacts With Myct1supporting
confidence: 93%
“…It was reported that CKAP4 plays important roles in several cellular processes, including endoplasmic reticulum anchoring 18 and morphology determination 19, regulation of Dicer function 20, cell proliferation 21 and tumour migration 22, 23. Knockdown of CKAP4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…APF inhibits Akt activity and proliferation in bladder cells through CKAP4 (Shahjee et al, ). In HCC cells, CKAP4 associates with EGF receptors and inhibits EGFR signalling, resulting in decreased proliferation and invasion capabilities (Li et al, ). It is unknown whether other CKAP4 ligands, such as SP‐A and tPA, are involved in the proliferation of these cancer cells.…”
Section: Dkk1 and Ckap4 Are Required For Cancer Cell Proliferationmentioning
confidence: 99%
“…As mentioned, a population of CLIMP-63 was reported to act as a cell-surface signaling receptor, indicative of its presence at the plasma membrane (18)(19)(20)(21)37). We investigated whether ZDHHC6 affects the abundance of CLIMP-63 at the plasma membrane using a surface biotinylation assay, wherein all surface proteins were chemically modified, isolated with streptavidin beads, and CLIMP-63 was subsequently identified by western blot.…”
Section: Climp-63 Is a Substrate For Zdhhc6 Which Regulates Its Plasmentioning
confidence: 99%
“…between two CLIMP-63 molecules present in opposing membrane patches "across" the ER lumen (6). CLIMP-63 has also been reported to be present at the plasma membrane, acting as a receptor for various ligands in a tissue-dependent manner (18)(19)(20)(21). How these different roles relate to each other, however, and how they are controlled is unknown.…”
Section: Introductionmentioning
confidence: 99%